Economic and Geographical Features of the Development and Location of the Textile Industry in Surkhandarya Region - Ergashev Sanjar Muhammadi O’g’li; Abdunazarov Husan Mengliyevich; Erdonov Muhammadi Nuralievich (Indonesian Journal of Public Policy Review, 2022)
This article discusses the economic and geographical features of the development and location of the textile industry in Surkhandarya region, in which the share of cotton area and clusters is analyzed.